Diplomat heroes of the Holocaust - Paldiʾel, Mordekhai (KTAV Publ. House, 2007)
Why diplomats : the significance of their action -- Nazi Germany : where it all began -- Lithuania : where is Curaçao ? -- France : to leave in a hurry ;l -- Denmark : an unforeseen miracle -- Warsaw, Genoa, and Rhodes : Yugoslav, Swedish, and Turkish diplomats ; -- Budapest : the apocalypse -- Also meriting mention and praise